Afro rizomas: corpo, noção de pessoa e identidade no Candomblé - Rezende, Marcos Vinícius Buiati (2016)
The body in Candomble, in its scenic and ritual performances, is asked to dwell friction zones that destabilize and confuse certain aesthetic-ethical-political normative standards. The aim of this study is to map part of this conjuncture of destabilization and displacements from the liturgical - teaching aspects in which the body is inserted in Candomble, in dialogue with some of the conceptual axes, such as aesthetics, composition, person, gender and identity. It seeks to elucidate in which ways the scenic and ritual performances of body in Candomble are only possible if there´s a destabilization of these normative categories, therefore creating an aesthetic - ethics of being in community through social and liturgical means that displaces and unsettles this body. The general theoretical scope rests on the rhizome perspective, epistemological system proposed by Deleuze and Guattari (1995), where there are no pre-established hierarchies or closed dichotomies. The approach so of the body in Candomblé is from a multi conceptual and hybrid reference. It also relies in Deleuze and Guattari (2010), Guattari (1992), Maffesoli (1996) and Santos (2012) to consider aesthetics in Candomble; Segato (2000), Goldman (1984) Butler (2012) and Hall (2011) for identity and notion of person. Theory and method are therefore interdisciplinary, thought from multiplicity and plurality conceptual and analytical, guided by cultural performances perspective. It is expected to show that body in Candomble´s performance builds a scenic act in itself, unique and inventive, as well as is in itself an event. So here, it can be said that in its plurality, body in Candomble affirms itself as revolutionary and subversive. It is a body that resists the present, questioning it from its margins and cracks.